An Instrument of Restructuring Policy to Overcome The Losses of District and City Public Drinking Water Companies in Jambi Province - Yuvanda, Sesraria; Rachmad R, Muhammad; Ihsan, Mohammad; Zulfanetti (Rescollacom (Research Collaborations Community), 2025)
The Regional Water Supply Company (in Indonesian it is called PERUMDAM) is a Regional Owned Enterprise or also known as BUMD, tasked with serving the community by providing clean water for both household and industrial consumption and seeking business profits. In reality, PERUMDAM still suffers losses in financial management despite its dual mandate. The purpose of this study is to examine the factors causing PERUMDAM's losses and formulate policies that can improve PERUMDAM's financial health through financial management in the province of Jambi. The analysis used is a panel data regression model and an in-depth panel data analysis model. The results of the study show that the variables of production cost, production efficiency, customer growth, and tariff fulfillment percentage are variables that significantly affect PERUMDAM losses and are priorities for policy formulation to improve PERUMDAM. Meanwhile, the variables of water loss and water meter replacement are variables that do not significantly affect PERUMDAM losses in districts/cities in Jambi Province. Policy instruments for addressing PERUMDAM losses can be implemented through three priority variables: reducing production cost, improving production efficiency, and increasing customer growth.